The Role of e-Trust in Mediating the Impact of Social Media Marketing via Instagram on e-Purchase Decisions - Fahreza, Ahmad; Hartanto, Prasetyo; Suryaningtias, Yosita Dwiani; Marsally, Silvia Van; Arum, Maliana Puspa (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This research explores how e-trust functions as an intermediary in the connection between marketing efforts on Instagram and customers’ decisions to buy online. The study uses a purposive sampling technique with a descriptive verification approach, involving an explanatory survey of 215 followers from the @bloodsclothofficial Instagram account, associated with Bloods Distro. Data were analyzed through path analysis using SPSS 25 software. The findings indicate that e-trust plays a significant role in mediating the relationship between Instagram marketing activities and e-purchase choices. These results highlight the need for businesses to enhance the quality of their Instagram-based marketing strategies to attract customers effectively, establish trust, and ultimately improve sales outcomes.